Na-doped LiMnPO4 as an electrode material for enhanced lithium ion batteries - Duraisamy, Navaneethan (Indian Academy of Sciences, 2017)
We report the influence of sodium (Na)-incorporated lithium manganese phosphate as an active material on its performance in electrochemical study for energy storage application. Li1-xNaxMnPO4 with different mole ratios (0.00 = x = 0.05) of sodium is synthesized via a simple sol-gel method. The discharge capacity of Li1-xNaxMnPO4 varies with respect to mole ratios of sodium incorporated. The maximum discharge capacity of 92.45 mAh g-1 is observed in Li0.97Na0.03MnPO4, which is higher than that of pristine LiMnPO4 and other Na-incorporated LiMnPO4. The maximum cyclic stability is found to be 84.15% up to 60 cycles. These results demonstrate that Li0.97Na0.03MnPO4 plays a significant role in future energy storage application.